An Assessment of Speaking Materials about Students’ Talking Etiquette by Using SCAS Model - Hayati Syafri; Amanda Maharani Putri (English Language Teaching and Research, 2017)
Many issues about the less talking etiquette of the students and the irreverence cases about the ways students do the communication in various conditions occur influenced by the multi-dimensional context. Innovation in speaking assessment is needed to fostering students‘ awareness of talking etiquette to overcome students’ issues in speaking class. It showed that the students have less speaking skill and the less knowledge about the important of talking etiquette. After all, the research aims to develop the speaking material modul and provide assessment about speaking that create new criteria; talking etiquette based on Socio-Cultural Affective Strategies (SCAS) model by inserting the target cultures in the speaking class. Interview and test are used in order to see how far the modul gives the contribution to improve students talking etiquette. Consequently, the assesment development about talking etiquette of the students for multi-dimensional context can positively give the effective result as the innovation in speaking material.Keywords: Assessment development, Talking etiquette, Multi-dimensional context, SCAS Model